Development of Android-based Listening Practice Application (FunNy-Fun&Handy) with Popular Culture Topic as An Innovative Learning Media - Damanik, Sisila Fitriany; Nasution, Nazlah Syahaf; Hasibuan, Juli Rachmadhani; Gintings, Immanuel Prasetya (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This research aims to develop an Android-based application as a learning medium for student exercises containing audio on popular cultures to practice their English listening skills. This research method used research and development with the ADDIE model, namely Analysis, Design, Development, Implementation, and Evaluation. Data was collected using a questionnaire for validators. A questionnaire was used to collect data for the application, material, and learning practitioner. In the development stage, the validators declare that this product was very valid and practical. It was shown that the scores given by the English lecturers were 91,4 and 90,4, and the Programmer validator gave it 94. Meanwhile, the average score collected from the practical sheet was 90. After the digital listening application was revised and evaluated, this product was stated as effective, showing that 4 students were in the B2-Upper Intermediate level, 12 students are in C1-Advance, 8 students were in C2-Proficient and no more students in the intermediate level. This app was appropriate for students to use as a platform to practice their listening skills outside the class.